2019
DOI: 10.4317/jced.56059
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nail biting, orthodontic treatment and Enterobacteriaceae in the oral cavity

Abstract: Background: Chronic nail biting is common in children and young adults. Auto inoculation of environmental pathogens can manifest as infection in distant organs. Multi-drug resistance gram negative bacteria are on the rise globally. Several of the foodborne bacteria fall within the Enterobacteriaceae family but very few studies have explored these microbes in the oral cavity of children with chronic nail-biting habit or orthodontic treatment. The study aims to investigate oral load of Enterobacteriaceae in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
13
0
4
Order By: Relevance
“…Previous studies have revealed that they may occur in high numbers and shift from transitory species to colonizers of the oral cavity in immunocompromised individuals (Simões-Silva et al 2018 ; Arirachakaran et al 2019 ). However, some studies have shown that they can colonize healthy subjects too (Ranganathan et al 2017 ; Chinnasamy et al 2019 ). Moreover, systemic colonization and infections associated with non-oral bacteria isolated from the oral cavity have been revealed (Arirachakaran et al 2019 ; Ghapanchi et al 2019 ), making the oral cavity an extra-hospital reservoir (Kearney et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that they may occur in high numbers and shift from transitory species to colonizers of the oral cavity in immunocompromised individuals (Simões-Silva et al 2018 ; Arirachakaran et al 2019 ). However, some studies have shown that they can colonize healthy subjects too (Ranganathan et al 2017 ; Chinnasamy et al 2019 ). Moreover, systemic colonization and infections associated with non-oral bacteria isolated from the oral cavity have been revealed (Arirachakaran et al 2019 ; Ghapanchi et al 2019 ), making the oral cavity an extra-hospital reservoir (Kearney et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among both IZC and Buccal Shelf implants , IZC was perceived to have only mild discomfort after placement [ Figure. 9]. however, this was not found to be statistically significant (p value -0.239) our extensive research expertise ranged from epidemiological studies to randomised clinical trials that have been published in reputed journals (Felicita, 2017a(Felicita, , 2017b(Felicita, , 2018Felicita, Thirumurthi and Jain, 2017;Korath, Padmanabhan and Parameswaran, 2017;Krishnan, Pandian and rajagopal, 2017;Charles et al, 2018;Pandian, Krishnan and Kumar, 2018;reddy et al, 2018;Chinnasamy et al, 2019). This knowledge was instrumental for us to assess the survival rate of extraalveolar TADs used for orthodontic anchorage.…”
Section: Resultsmentioning
confidence: 99%
“…Our extensive research expertise ranged from epidemiological studies to randomised clinical trials that have been published in reputed journals(felicita, 2017a, 2017b, 2018; felicita, Thirumurthi and Jain, 2017; korath, Padmanabhan and Parameswaran, 2017; krishnan, Pandian and rajagopal, 2017;Charles et al, 2018;Pandian, krishnan and kumar, 2018;reddy et al, 2018;Chinnasamy et al, 2019). This knowledge was instrumental for us to compare the plaque retention in ceramic and metal brackets.…”
Section: Resultsmentioning
confidence: 99%